Sex Recession: Challenges and Threats for the Economy - Lusiana Lusiana; Fauziah Fauziah; Wasti Indah Haryani Daulay (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
The term